RECOMMENDATIONS FOR THE TREATMENT OF ACNE, SUMMARISED ACCORDING TO THE LATEST INTERNATIONAL GUIDELINES - Manca Valjavec; Mateja Starbek Zorko (The Society for Children with Metabolic Disorders, 2021)
Acne vulgaris is a common, chronic skin disease that can occur in people of all ages, most commonly in teenagers. Acne occurs on the seborrhoeic areas of the skin, most often on the face, hence it can have a signiﬁcant impact on the patient's quality of life, and it can be the cause of associated psychological problems and disorders. There are four important pathogenetic factors in the pathogenesis of acne that are key therapeutic targets. In the review article, we present the clinical picture of acne and staged treatment, which has been summarised according to the European and American guidelines for the treatment of acne. We present the local and systemic treatment and other treatment methods, which should always be individually tailored to the patient and dependent on the severity of the disease, gender, age and associated diseases.